A mixed-integer linear programming model for scheduling volunteers in technical support teams in Non-Governmental Organizations - Valdir Soares Silva Neto; Ricardo Lukas de Medeiros França; Keren Karolyne Nóbrega Silva; Luciano Carlos Azevedo da Costa; Hugo Harry F. R. Kramer (Socioeconomic Analytics)
The problem of allocating scarce resources is present in many daily decisions, at various levels, whether organizational or not. Institutions need to plan in detail how to distribute resources efficiently, especially when it comes to people and their skills and competencies in providing services. In this context, the aim of this study is to determine timetables for the volunteers of a technical support team in a non-governmental organization, considering the individual skills constraints of the volunteers and their respective availability. To solve the problem, a mathematical model is proposed whose objective is to allocate volunteers to tasks for which they have the greatest ability. The model ensures that the technical needs of the team are met, guaranteeing the allocation of specific numbers of volunteers to each role. The model also favors a balanced distribution of work among the volunteers. The results show that the proposed model can find optimal solutions in reduced computational time. The solutions generated by the proposed model are already being implemented and used in practice.